2020
DOI: 10.1111/ejh.13482
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prevalence and outcome of cardiovascular events in the first 100 days postallogeneic hematopoietic stem cell transplant

Abstract: Introduction Recent advances in allogeneic hematopoietic stem cell transplant (HSCT) have allowed us to offer HSCT to older, advanced disease patients with more co‐morbidities. Cardiovascular toxicity post‐transplant is a major concern due to the increased risk of mortality. Few studies have examined the prevalence of CV events including CAD (MI, angina, PCI, CABG, CHF, arrhythmias), HTN, stroke/TIA, and death in the first 100 days post‐transplant. Patients We assessed the impact of pretransplant MUGA results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…[ 23 ] Our multivariable analysis showed that post-CCVD was significantly affected by pre-CCVD ( P < 0.001). Alblooshi et al [ 24 ] recently demonstrated that a history of CV disease, myocardial infarction, or CAD was the most important predictor of CV events in the first 100 days after HCT ( P = 0.00002). A controlled study found that cardiac autonomic functioning was impaired 1 to 10 years after allo-HCT, which may be associated with post-CCVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23 ] Our multivariable analysis showed that post-CCVD was significantly affected by pre-CCVD ( P < 0.001). Alblooshi et al [ 24 ] recently demonstrated that a history of CV disease, myocardial infarction, or CAD was the most important predictor of CV events in the first 100 days after HCT ( P = 0.00002). A controlled study found that cardiac autonomic functioning was impaired 1 to 10 years after allo-HCT, which may be associated with post-CCVD.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in the median days of neutrophil (14 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] vs. 12 [9-21] days, P = 0.269) and platelet (14 vs. 14 days, P = 0.395) engraftment between the pre-CCVD group and the control group. In the multivariable analysis, rapid neutrophil recovery was associated with a greater number of infused CD34 + cells (P = 0.016) and disease status in remission (P = 0.002).…”
Section: Outcomes Of Transplantationmentioning
confidence: 99%
“…DNJ is the main ingredient of ML and serum levels of DNJ had a strong negative relationship with the MAX IMT values (Figure 7). The severity of carotid atherosclerosis is often evaluated by MAX IMT (Alblooshi et al., 2020). Thus, ML attenuated atherosclerotic lesions possibly via its main ingredient DNJ.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical outcome included the occurrence of cerebrovascular and cardiovascular events and measured after a 12‐month intervention. The events included cardiovascular death; nonfatal myocardial infarction; nonfatal cerebral stroke excluding transient ischemic attack; hospital admission and all coronary revascularizations with either PCI or CABG (Alblooshi et al., 2020; Bonsu et al., 2020; Yamashita et al., 2020; You et al., 2020). The following parameters were also measured, including survival time without events, the values of the intima–media thickness (IMT) of carotid arteries, and severe side effects and their frequency.…”
Section: Methodsmentioning
confidence: 99%
“…The risk of stroke is 15 × higher than in the general population [ 87 ]. Three recent series [ 88 90 ] found low frequencies of both of PRES (4%) and stroke (< 1% in the first 100 days [ 79 ] to 10% in longer follow-up). While PRES usually occurs early (up to 100 days) after transplantation, ischemic stroke may occur early, late (up to 2 years), or very late, while intracerebral hemorrhage happens predominantly early on [ 88 ].…”
Section: Cerebrovascular Complications Of Treatments Of Hematological Diseasesmentioning
confidence: 99%